2007
DOI: 10.2134/agronj2007.0085
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Responses of Sugarcane to Long‐Term Flooding

Abstract: Sugarcane (Saccharum spp.) in south Florida is often subjected to flooding due to intense summer rainfall or tropical storms. While there has been considerable research on the response of sugarcane cultivars to high water tables, there is a lack of information on cultivar morphological adaptation to long-term flooding. An experiment was established in Belle Glade, FL to examine: (i) effects of a July-September flood on the morphological characters of cv. CP 80-1743 and CP 72-2086 and (ii) significant flood 3 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 14 publications
2
21
0
6
Order By: Relevance
“…Plants exposed to 60 d of flooding showed a slightly decreased growth rate in all the sugarcane cultivars and Erianthus. This result was related to the findings of previous studies that flooding inhibited leaf expansion and decreased LA, LAI, and leaf weight (Gilbert et al, 2007;Gomathi et al, 2014;Jaiphong et al, 2016), whereas flooding for < 3 mo less damaged LAI (Gilbert et al, 2008). Flooding also decreased stem weight on 90 DAT, which is consistent with a previous finding that water logging over 15-60 d at the grand growth phase decreased yield by approximately 5-30% because of the lack of nutrition and water uptake (Gomathi et al, 2014), while 3 mo of flooding decreased the yield by 18-37% in plant cane and 61-63% in a second ratoon (Gilbert et al, 2008).…”
Section: Sugar Content and Sugar Yieldsupporting
confidence: 89%
See 1 more Smart Citation
“…Plants exposed to 60 d of flooding showed a slightly decreased growth rate in all the sugarcane cultivars and Erianthus. This result was related to the findings of previous studies that flooding inhibited leaf expansion and decreased LA, LAI, and leaf weight (Gilbert et al, 2007;Gomathi et al, 2014;Jaiphong et al, 2016), whereas flooding for < 3 mo less damaged LAI (Gilbert et al, 2008). Flooding also decreased stem weight on 90 DAT, which is consistent with a previous finding that water logging over 15-60 d at the grand growth phase decreased yield by approximately 5-30% because of the lack of nutrition and water uptake (Gomathi et al, 2014), while 3 mo of flooding decreased the yield by 18-37% in plant cane and 61-63% in a second ratoon (Gilbert et al, 2008).…”
Section: Sugar Content and Sugar Yieldsupporting
confidence: 89%
“…Sugarcane growth has been shown to be restricted via decrease in metabolic activity of roots because of hypoxia occurring during flood conditions (Gomathi et al, 2014). Plants adapt to flooding by developing adventitious roots with well-developed aerenchyma to assist the maintenance of root activity and the supply of required oxygen, and also contribute to higher dry matter accumulation (Drew, 1997;Gilbert et al, 2007;Gomathi et al, 2014;Jaiphong et al, 2016).…”
mentioning
confidence: 99%
“…It has previously been reported that flooding for 3 mo led to a 4-15 times increase in root development, a 108% greater aerenchyma pipe extension, and a 115% greater aerenchyma pipe diameter (Gilbert et al, 2007), while flooding for 120 d to a level 30 cm above the top of the soil led to sugarcane clone I 6-04 having the highest root dry weight at 28.3 g/plant (Begum et al, 2013). During floods, plants produce roots and exhibit ethylene-dependent death and lysis, which lead to the formation of continuous gas-filled channels (aerenchyma) that help the plants to maintain their root activity and supply the necessary oxygen (Drew, 1997).…”
Section: Resultsmentioning
confidence: 97%
“…Thus, the numerous roots that grow during floods are better adapted to these conditions than the original roots, containing well-developed aerenchyma (Laan et al, 1991). Since root elongation was closely related to the oxygen concentration in the root zone, the internal aeration of the plants may have been achieved by increasing the root porosity and developing aerenchyma, which may have helped the plants to continue to take up water and nutrients, and may have offset any losses associated with flooding (Begum et al, 2013;Gilbert et al, 2007;Gomathi et al, 2014). However, following drainage, it was found that some of the original roots were damaged, and the adventitious roots dried out and became non-functional.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation